2006
DOI: 10.1088/0022-3727/39/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of ZnO thin films on Si substrate with and without ITO buffer layer

Abstract: Photoluminescence (PL) properties of ZnO thin films on Si substrate with and without an indium tin oxide (ITO) buffer layer, prepared under different oxygen partial pressures in the sputtering gas, were studied. It was found that PL characteristics of ZnO thin films depend on oxygen partial pressure and substrate, and the PL peak in the ultraviolet region has a strong red-shift with increasing excitation intensity on the glass and Si substrates with the ITO buffer layer, and the PL intensity increases with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 34 publications
(29 reference statements)
2
25
0
Order By: Relevance
“…Thus exciton may be observed at room temperature. In our case the excitonic level emission around 386 nm for the ZnO film on quartz substrate is very close to that reported value of 380 nm excitonic recombination for Si substrate [13] corresponding to the free exciton. However, in case of glass substrate no UV emission peak was observed.…”
Section: Photoluminescence (Pl)supporting
confidence: 90%
See 1 more Smart Citation
“…Thus exciton may be observed at room temperature. In our case the excitonic level emission around 386 nm for the ZnO film on quartz substrate is very close to that reported value of 380 nm excitonic recombination for Si substrate [13] corresponding to the free exciton. However, in case of glass substrate no UV emission peak was observed.…”
Section: Photoluminescence (Pl)supporting
confidence: 90%
“…Besides, substrates affect the luminescence behaviour of the material. Teng et al had reported the PL in the UV region at~380 nm (UV-PL) from ZnO thin film grown on Si substrate [13]. This emission peak shifts to 395 nm for the sample grown on ITO/Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al 2002;Kang et al 2004;Teng et al 2006), the observation is unusual. It may be noted that the…”
mentioning
confidence: 88%
“…ZnO thin film grown on ITO covered glass substrate exhibits good crystal quality resulting from a small lattice mismatch (3%) between the neighboring oxygen-oxygen (O-O) distance on the close-packed (1 1 1) plane of ITO and (0 0 1) plane of ZnO [9]. Therefore, we propose that combining the high conductive ITO film as seed layer with MOCVD-ZnO films maybe is an effective way to obtain high quality TCO films.…”
Section: Introductionmentioning
confidence: 99%